If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 6w + 18 Reorder the terms: -12 = 18 + 6w Solving -12 = 18 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. -12 + -6w = 18 + 6w + -6w Combine like terms: 6w + -6w = 0 -12 + -6w = 18 + 0 -12 + -6w = 18 Add '12' to each side of the equation. -12 + 12 + -6w = 18 + 12 Combine like terms: -12 + 12 = 0 0 + -6w = 18 + 12 -6w = 18 + 12 Combine like terms: 18 + 12 = 30 -6w = 30 Divide each side by '-6'. w = -5 Simplifying w = -5
| 6x-10=28 | | 5x+3y=176 | | k+40=8(k+5) | | M-42=19 | | 4a-6=2a-4 | | 4x+2+x=-10 | | N-5*.66=.75 | | 2x+7-10=3 | | 2(x+1)+34=-4 | | 3x+(-6)=6 | | 3x+1=35 | | -5x+7(-4x+17)=-178 | | 3(a+1)=4(a-1.5) | | 50t=0.25t+1000 | | -2x+121=0 | | h=-16t^2+48t+7 | | 8+x=3Xx | | 5p+2p-3p= | | -8+5x=3+7(x-1) | | Y-4=5y | | -7=3x | | -125=5(w-12) | | 15b-14a+5b+16a= | | 6(1-6x)=-25-5x | | 3(2y+5)=11 | | 14+d-6=7 | | Y-5=-(4-y) | | 12w=16(w-8) | | -75m=15 | | a^4+2a^2-3=0 | | -49=a+5 | | 5b+12=-5 |